Biological additive-containing composite electrolyte for aqueous zinc ion battery
By adding adenine nucleoside to the electrolyte of an aqueous zinc ion battery, the solvated structure of zinc ions and the interface behavior between the electrolyte and the zinc surface are changed, and the problems of hydrogen evolution reaction, zinc negative electrode corrosion and zinc dendrites are solved, which significantly improves the cycling performance and stability of the battery.
Patent Information
- Application Number
- CN202510074384.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-03-18
AI Technical Summary
The existing aqueous zinc ion batteries have problems such as hydrogen evolution reaction, corrosion of zinc negative electrodes, and growth of zinc dendrites, which limit their commercial applications.
A composite electrolyte composed of water-soluble zinc salt containing adenine nucleoside is used to change the solvated structure of zinc ions and the interface behavior between the electrolyte and the zinc surface through the interaction between the adenine nucleoside and zinc ions and water molecules, and inhibit side reactions and dendrites.
It effectively inhibits the hydrogen evolution reaction and corrosion of zinc negative electrode, slows down the growth of zinc dendrites, and significantly improves the circulation performance and stability of zinc ion batteries.
Smart Images

Figure CN119650894A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aqueous zinc ion batteries, and in particular to a composite electrolyte for aqueous zinc ion batteries containing a biological additive. Background Art
[0002] Against the backdrop of the depletion of fossil fuels and increasingly severe environmental problems, environmental and energy issues have become an important focus of the future development of human society. Reducing dependence on fossil fuels and strengthening ecological environmental protection is an inevitable trend. For this reason, people have gradually turned their attention to the development and utilization of new energy. New energy sources such as solar energy and wind energy can be continuously converted into electricity, but the storage and large-scale application of such electricity are limited by economic costs, and energy storage issues are becoming a strategic issue. Secondary batteries are considered to be the most promising electrochemical energy storage devices, among which lithium-ion batteries have the advantages of good cycle stability and high energy density, and currently occupy a dominant position in the rechargeable battery market. However, lithium resources are limited and costly, and the use of its organic electrolyte is accompanied by serious safety issues, which greatly hinders the promotion and large-scale application of lithium-ion batteries. Compared with lithium-ion batteries using organic electrolytes, aqueous metal ion batteries have the advantages of better safety and lower cost, and show great application potential in the field of energy storage. Zinc has a low redox potential (-0.762V relative to the standard hydrogen electrode). When metallic zinc is used as the negative electrode, it is well compatible with aqueous electrolytes (alkaline, neutral, weakly acidic) and has good stability. Zinc resources are extremely abundant, with confirmed zinc resources estimated to exceed 1.9 billion tons. In addition, zinc has the advantages of high theoretical capacity, high specific capacity, high safety and environmental friendliness, so aqueous zinc ion batteries (ZIBs) are expected to become the most promising new energy storage device.
[0003] However, problems such as dendrite growth, hydrogen evolution and corrosion of zinc anodes limit their commercial application. Anode structure adjustment, electrolyte system regulation and diaphragm modification have been proposed to solve these problems of zinc anodes. Among them, adding additives to the electrolyte is the most convenient and effective way to improve the performance of zinc-ion batteries. Therefore, it is crucial to design a green, low-cost and effective electrolyte additive. Summary of the invention
[0004] The purpose of the present invention is to provide a composite electrolyte for an aqueous zinc ion battery containing a bio-type additive, so as to solve the technical problems of hydrogen evolution reaction, corrosion of zinc negative electrode and zinc dendrite growth existing in the existing aqueous zinc ion batteries.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention firstly provides a composite electrolyte for an aqueous zinc ion battery containing a biological additive. The composite electrolyte consists of a water-soluble zinc salt, deionized water and the biological additive, and the biological additive is adenine nucleoside.
[0007] Furthermore, in the composite electrolyte, the concentration of the water-soluble zinc salt is 0.1-3.0 mol L -1 The concentration of adenine nucleoside additive is 0.5-3 g L -1 .
[0008] Furthermore, the water-soluble zinc salt is at least one of zinc sulfate, zinc acetate, zinc trifluoromethanesulfonate, zinc chloride and zinc perchlorate.
[0009] The present invention also provides a method for preparing the composite electrolyte for aqueous zinc ion batteries, comprising the following steps:
[0010] Step 1: dissolving a water-soluble zinc salt in deionized water to obtain a basic electrolyte;
[0011] Step 2: Add adenine nucleoside additive to the above basic electrolyte, sonicate until completely dissolved, and let stand to obtain an aqueous zinc ion battery composite electrolyte containing a bio-type additive.
[0012] The present invention further provides an aqueous zinc ion battery, wherein the electrolyte of the aqueous zinc ion battery adopts the composite electrolyte containing the above-mentioned bio-type additive. The aqueous zinc ion battery can be a zinc-zinc symmetric battery, a zinc-copper asymmetric half-cell or a full battery.
[0013] Furthermore, the zinc-zinc symmetrical battery is composed of commercial zinc foil, a glass fiber separator and the composite electrolyte.
[0014] Furthermore, the zinc-copper asymmetric half-cell is composed of commercial zinc foil, a glass fiber separator, commercial copper foil and the composite electrolyte.
[0015] Furthermore, the full battery is composed of a commercial zinc foil as a negative electrode, a glass fiber separator, a composite material of iodine and activated carbon as a positive electrode, and the composite electrolyte.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] (1) The present invention uses adenosine as a biological additive for aqueous zinc ion battery electrolyte. Compared with water molecules, adenosine has a higher affinity for Zn 2+ Has a stronger affinity and can change Zn[(H2O)6] 2+ The solvation structure of H2O can be reduced and the activity of H2O can be reduced, thereby inhibiting side reactions such as hydrogen evolution.
[0018] (2) The present invention uses adenosine nucleoside as a biological additive for aqueous zinc ion battery electrolyte. Adenosine nucleoside can be adsorbed on the surface of zinc anode to form a nitrogen-rich protective layer, provide abundant nucleation sites, and accelerate ion transport and desolvation processes. In addition, adenosine nucleoside adsorbed on the surface of zinc anode will change the original double electric layer EDL, replace water molecules in the inner Helmholtz layer IHL, and form a water-poor IHL, thereby inhibiting water-related side reactions.
[0019] (3) The present invention uses adenosine nucleoside as a biological additive for aqueous zinc ion battery electrolyte. Compared with water molecules, adenosine nucleoside has a greater adsorption energy with the zinc (002) crystal surface, so it will be preferentially adsorbed on the zinc (002) crystal surface, guiding zinc ions to deposit uniformly on the (002) crystal surface, thereby inhibiting the growth of zinc dendrites during the electrochemical cycle.
[0020] (4) The adenine nucleoside additive of the present invention is green, pollution-free, low-cost, and has a significant effect on extending the cycle life, and has good practical prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the Fourier transform infrared spectra of different electrolytes;
[0022] Figure 2 is the chronoamperometric (CA) curve of Zn / / Zn symmetric cells assembled with different electrolytes;
[0023] Figure 3 The Zn / / Zn symmetric battery assembled with different electrolytes at 5 mA cm -2 Time-voltage curves under current density;
[0024] Figure 4 It is the time-voltage curve of Zn / / Zn symmetric battery assembled with different electrolytes at 60% discharge depth;
[0025] Figure 5 The Zn / / Cu asymmetric battery assembled with different electrolytes has a high performance at 1 mA cm -2 Coulomb efficiency comparison curve under current density;
[0026] Figure 6 It is the linear sweep voltammetry (LSV) curve of Zn / / Cu asymmetric cells assembled with different electrolytes;
[0027] Figure 7 The zinc-zinc symmetrical battery assembled with the comparative electrolyte is 5 mA cm -2 Scanning electron microscope (SEM) image of the zinc electrode after cycling for 30 hours at a current density of ;
[0028] Figure 8The zinc-zinc symmetrical battery assembled with the electrolyte of Example 2 was -2 Scanning electron microscope (SEM) image of the zinc electrode after cycling for 30 hours at a current density of ;
[0029] Fig. 9 It is a Zn / / I2 full battery assembled with different electrolytes at 1Ag -1 Comparison of discharge specific capacity and charge and discharge efficiency under current density. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions of the present invention are further described below in conjunction with specific embodiments. The following embodiments are implemented on the premise of the technical solutions of the present invention, and detailed implementation methods and specific operating processes are given, but the protection scope of the present invention is not limited to the following embodiments.
[0031] Example 1
[0032] This embodiment prepares a composite electrolyte for aqueous zinc ion batteries according to the following steps:
[0033] Step 1: dissolving zinc sulfate heptahydrate powder in deionized water to obtain a basic electrolyte;
[0034] Step 2: Add adenosine nucleoside to the basic electrolyte, ultrasonicate for 1 hour, and let stand for 12 hours to obtain a composite electrolyte in which the concentration of zinc sulfate is 2.0 mol L -1 The concentration of adenine nucleoside was 0.5 g L -1 .
[0035] Example 2
[0036] In this embodiment, a composite electrolyte for aqueous zinc batteries is prepared according to the following steps:
[0037] Step 1: dissolving zinc sulfate heptahydrate powder in deionized water to obtain a basic electrolyte;
[0038] Step 2: Add adenosine nucleoside to the basic electrolyte, ultrasonicate for 1 hour, and let stand for 12 hours to obtain a composite electrolyte in which the concentration of zinc sulfate is 2.0 mol L -1 , the concentration of adenosine was 1.5 g L -1 .
[0039] Example 3
[0040] In this embodiment, a composite electrolyte for aqueous zinc batteries is prepared according to the following steps:
[0041] Step 1: dissolving zinc sulfate heptahydrate powder in deionized water to obtain a basic electrolyte;
[0042] Step 2: Add adenosine nucleoside to the basic electrolyte, ultrasonicate for 1 hour, and let stand for 12 hours to obtain a composite electrolyte in which the concentration of zinc sulfate is 2.0 mol L -1 , the concentration of adenosine is 3 g L -1 .
[0043] Comparative Example
[0044] The electrolyte provided in this comparative example is a basic electrolyte obtained by dissolving zinc sulfate heptahydrate powder in deionized water, wherein the concentration of zinc sulfate is 2.0 mol L -1 .
[0045] In order to test the practical performance of the electrolytes prepared in the embodiments and comparative examples, batteries were assembled and battery performance tests were performed according to the following method:
[0046] Place the zinc sheet into the negative electrode shell, then into the glass fiber separator, add an appropriate amount of electrolyte, stack the zinc / copper / iodine and activated carbon composite positive electrode sheet, gasket and shrapnel in sequence, cover the positive electrode shell, and finally place it into a button battery packaging machine to seal it into a zinc-zinc symmetrical battery / zinc-copper asymmetric half-cell / full battery.
[0047] Figure 1 is the Fourier infrared spectrum of different electrolytes. Figure 1 It can be concluded that, compared with the comparative example, after the addition of adenine nucleoside additive, the vibration stretching peak corresponding to the sulfate group blue-shifted, which indicates that the interaction between zinc ions and sulfate groups is enhanced and the solvation structure of zinc ions is destroyed.
[0048] In order to explore the effect of different electrolytes on the diffusion mode of zinc ions, a zinc-zinc symmetric battery with different electrolytes was assembled using a 100 μm thick commercial zinc foil for it curve measurement. The results are shown in Figure 2 As shown, it can be concluded that the current density of the zinc-zinc symmetric battery assembled with the 2M ZnSO4 electrolyte without additives in the comparative example continues to increase rapidly, indicating that the zinc ions are undergoing a disorderly two-dimensional diffusion, resulting in uneven zinc nucleation. However, the current density of the zinc-zinc symmetric battery assembled with the electrolyte containing adenine nucleoside gradually stabilizes after only a short nucleation process of 10s, and a stable and continuous three-dimensional diffusion process begins, indicating that the addition of adenine nucleoside is conducive to the uniform deposition of zinc.
[0049] Depend on Figure 3It can be concluded that the zinc-zinc symmetric battery (using a zinc sheet with a thickness of 100 μm) assembled with a 2M ZnSO4 electrolyte without additives in the comparative example was cycled for only about 51 hours before the polarization voltage began to decrease rapidly, indicating that a large amount of corrosion products and dendrites were generated, causing the battery to fail. However, the zinc-zinc symmetric battery assembled with the electrolyte containing adenine nucleoside additive in Example 2, because adenine nucleoside changes the zinc ion solvation structure and EDL, inhibits the corrosion reaction, and guides the uniform deposition of zinc ions in the electrochemical cycle, inhibits the growth of dendrites, and finally enables the zinc-zinc symmetric battery to stably cycle for more than 1000 hours.
[0050] Depend on Figure 4 It can be concluded that: the zinc-zinc symmetrical battery (using a zinc sheet with a thickness of 10 μm) assembled with a 2M ZnSO4 electrolyte without additives in the comparative example has a sudden drop in polarization voltage and a short circuit in the battery after cycling for 25 hours at a high depth of discharge of 60%. However, the zinc-zinc symmetrical battery assembled with the electrolyte containing adenine nucleoside additive in Example 2 can stably cycle for more than 190 hours at a high depth of discharge of 60%, indicating that the adenine nucleoside additive has a good protective effect on the zinc anode.
[0051] Depend on Figure 5 It can be concluded that the zinc (using zinc sheet thickness of 100 μm) copper asymmetric battery assembled by the comparative example using 2M ZnSO4 electrolyte without additives has a coulombic efficiency value of 0 after 110 cycles, indicating that the battery is invalid. However, the zinc-copper asymmetric battery assembled by the electrolyte containing adenine nucleoside additive in Example 2 can stably cycle 420 cycles, indicating that the electrochemical performance of the battery has been greatly improved under the multiple functions of adenine nucleoside.
[0052] In order to explore the effect of different electrolytes on the hydrogen evolution overpotential, zinc (using zinc sheet thickness of 100μm) copper asymmetric cells with different electrolytes were assembled for LSV curve measurement. Figure 6 It can be concluded that the hydrogen evolution overpotential of the zinc-copper asymmetric battery assembled in the comparative example using a 2M ZnSO4 electrolyte without additives is -0.056V, while the hydrogen evolution overpotential of the zinc-copper asymmetric battery assembled using an electrolyte containing adenine nucleoside additives at the same current density is significantly improved, indicating that the addition of adenine nucleoside additives increases the hydrogen evolution overpotential, which is beneficial to inhibiting the evolution of hydrogen.
[0053] The zinc-zinc symmetric battery (using a zinc sheet with a thickness of 100 μm) assembled with the electrolytes of the comparative example and Example 2 was -2 The scanning electron microscope (SEM) images of the zinc electrode after cycling for 30 hours at a current density of Figure 7 and Figure 8 shown. Figure 7The zinc anode surface of (Comparative Example) is rough and loose, with severe dendrites and corrosion products. Figure 8 The surface of the zinc anode of (Example 2) is flat and smooth, without dendrites and byproducts, indicating that the adenine nucleoside additive successfully inhibits corrosion reactions and dendrite growth.
[0054] Using 100 μm commercial zinc foil as the negative electrode and a composite material of iodine and activated carbon as the positive electrode, the electrolytes of Example 2 and the comparative example were assembled into full batteries for charge and discharge cycle tests. The comparison of the discharge specific capacity and charge and discharge efficiency is shown in the figure below. Fig. 9 As shown. Fig. 9 It can be seen that compared with the full battery using 2M ZnSO4 electrolyte without additives, the full battery assembled with electrolyte added with adenosine nucleoside has a higher discharge specific capacity and still has a higher capacity retention after 4000 cycles.
[0055] From the above content, it can be seen that the bio-type electrolyte additive provided by the present invention can adjust the solvation structure of zinc ions and the interface behavior between the electrolyte and the zinc surface, effectively solving problems such as zinc dendrites, zinc metal corrosion and hydrogen evolution, thereby greatly improving the cycle performance of the zinc negative electrode.
[0056] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.
Claims
1. A composite electrolyte for aqueous zinc ion batteries containing a bio-based additive, characterized in that: The aqueous zinc ion battery composite electrolyte comprises: a water-soluble zinc salt, deionized water and an adenine nucleoside additive.
2. The composite electrolyte for aqueous zinc ion batteries according to claim 1, characterized in that The concentration of the water-soluble zinc salt in the composite electrolyte is 0.1-3 mol L -1 The concentration of adenine nucleoside additive is 0.5-3 g L -1 .
3. The composite electrolyte for aqueous zinc ion batteries according to claim 1, characterized in that: The water-soluble zinc salt is at least one of zinc sulfate, zinc acetate, zinc trifluoromethanesulfonate, zinc chloride and zinc perchlorate.
4. A method for preparing a composite electrolyte for an aqueous zinc ion battery according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: dissolving a water-soluble zinc salt in deionized water to obtain a basic electrolyte; Step 2: Add adenine nucleoside to the basic electrolyte, sonicate until it is completely dissolved, and let it stand to obtain a composite electrolyte for aqueous zinc ion batteries containing a bio-type additive.
5. An aqueous zinc ion battery, characterized in that: The composite electrolyte according to any one of claims 1 to 3 is used.
Citation Information
Patent Citations
Aqueous zinc ion battery electrolyte of small organic molecule additive containing amino and hydroxyl as well as preparation method and application of aqueous zinc ion battery electrolyte
CN116565347A